2006
DOI: 10.1007/s00383-006-1643-6
|View full text |Cite
|
Sign up to set email alerts
|

The immediate and long-term outcomes of newborns with congenital diaphragmatic hernia

Abstract: In spite of the innovations in the management of newborns with congenital diaphragmatic hernia (CDH) presenting with respiratory distress at birth, mortality and ongoing morbidity still remain high. This is a retrospective analysis of newborns with CDH to determine the immediate and long-term outcomes among survivors. Medical records of newborns with CDH and respiratory distress at birth between January 1993 and March 2002 were reviewed retrospectively. There were 45 newborns, 29 males and 16 females. Eleven n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…Keller et al [43] [48,[59][60][61]. Bronchodilators and inhaled steroids were, at least transiently, used by the majority of CDH patients, during the first year of life and thereafter [61,62]. In other studies, however, none of the participating children had significant respiratory symptoms [63,64], suggesting that CDH patients were doing well, regarding long-term pulmonary outcome.…”
Section: Fetal Tracheal Occlusionmentioning
confidence: 98%
See 1 more Smart Citation
“…Keller et al [43] [48,[59][60][61]. Bronchodilators and inhaled steroids were, at least transiently, used by the majority of CDH patients, during the first year of life and thereafter [61,62]. In other studies, however, none of the participating children had significant respiratory symptoms [63,64], suggesting that CDH patients were doing well, regarding long-term pulmonary outcome.…”
Section: Fetal Tracheal Occlusionmentioning
confidence: 98%
“…Effects on pulmonary function of CDH patients treated with fetal TO are preliminary. Keller et al [43] [48,[59][60][61]. Bronchodilators and inhaled steroids were, at least transiently, used by the majority of CDH patients, during the first year of life and thereafter [61,62].…”
Section: Fetal Tracheal Occlusionmentioning
confidence: 99%
“…The infant with a large diaphragmatic defect or need for ECMO is at greatest risk. [27][28][29][30][31][32][33][34][35][36] Nobuhara et al 27 reported developmental delay in more than 33% of their CDH survivors. McGahren et al 30 described neurologic abnormalities in 67% of infants with CDH who were treated with ECMO compared with 24% of infants with CDH who were not as ill and did not receive ECMO.…”
Section: Neurocognitive Delay and Behavioral Disordersmentioning
confidence: 99%
“…Pulmonary hypoplasia installs during prenatal development [2][3][4] and limited possibilities exist to attenuate it [5,6] . PH is likely secondary to pulmonary hypoplasia and associated underdeveloped vascular bed, which for some authors is a major determinant of postnatal clinical outcome [7] . For this reason, evaluation of PH severity is considered important for management of CDH infants in several centers [1] and its assessment is crucial to decide upon pulmonary vasodilator therapy as well as to monitor its effects [8,9] .…”
Section: Introductionmentioning
confidence: 99%